Latent structure of negative valence measures in childhood. Issue 8 (22nd May 2017) - Lee, Minyoung; Aggen, Steven H.; Carney, Dever M.; Hahn, Shannon; Moroney, Elizabeth; Machlin, Laura; Brotman, Melissa A.; Towbin, Kenneth E.; Leibenluft, Ellen; Pine, Daniel S.; Roberson‐Nay, Roxann; Hettema, John M.
Abstract : Background: Internalizing disorders (IDs), consisting of the syndromes of anxiety and depression, are common, debilitating conditions often having onsets in adolescence. Scientists have developed dimensional self‐report instruments that assess putative negative valence system (NVS) trait‐like constructs as complimentary phenotypes to clinical symptoms. These include various measures that index temperamental predispositions to IDs and correlate with neural substrates of fear, anxiety, and affective regulation. This study sought to elucidate the overarching structure of putative NVS traits and their relationship to early manifestations of ID symptomatology. Methods: The sample consisted of 768 juvenile twin subjects ages 9–13. Together with ID symptoms, extant validated instruments were chosen to assess a broad spectrum of NVS traits: anxiety sensitivity, irritability, fearfulness, behavioral activation and inhibition, and neuroticism and extraversion. Exploratory and confirmatory factor analyses (EFA/CFA) were used to investigate the latent structure of the associations among these different constructs and ID symptoms. Bifactor modeling in addition to standard correlated‐factor analytic approaches were applied. Results: Factor analyses produced a primary tripartite solution comprising anxiety/fear, dysphoria, and positive affect among all these measures. Competing DSM‐like correlated factors and an RDoC‐like NVS bifactor structure provided similar fit to these data. Conclusions: Our findings support the conceptual organization of a tripartite latent internalizing domain in developing children. This structure includes both clinical symptoms and a variety of self‐report dimensional traits currently in use by investigators. These various constructs are, therefore, most informatively investigated using an inclusive, integrated approach.